THE ATTACK of Rastrococcus sp. (Hemiptera: Pseudococcidae) ON Dysoxylum mollissimum Blume IN CAMPUS FOREST OF BENGKULU UNIVERSITY - Ginting, Sempurna; ., Nadrawati; Zarkani, Agustin; Depari, Efratenta (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
ysoxylum mollissimum is a commodity that is widely used as carpentry wood and furniture in Bengkulu. Rastrococcus sp. is one of the pests of D. mollissimum. The purpose of this study was to evaluate the attack of Rastrococcus sp. on saplings, poles and trees D. mollissimum in the campus forest of Bengkulu University. The study was conducted with a purposive sampling survey method. The observational variables were symptoms and the rate of attack of Rastrococcus sp. at various stages of growth, the host range, and the identification of natural enemies of Rastrococcus sp. The results showed that Rastrococcus sp. was able to attack D. mollissimum at all growing stages, namely sapling, pole and tree. The highest number of Rastrococcus sp. population was observed in the pole phase (35.4 ± 6.46 individuals), then the tree phase (34.9 ± 20.38 individuals), and saplings (26.3 ± 5.12 individuals). The Rastrococcus sp. was commonly found in the lower leaves. Scymnus sp. (Coleoptera: Coccinellidae) and Acarina (mites) were found as predator of the mealybug. This information is expected to be a reference in developing control strategies of Rastrococcus sp. especially on D. mollissimum.